2001
DOI: 10.1124/mol.60.5.989
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Inositol 1,4,5-Trisphosphate Receptor Is Essential for the Opening of Mouse TRP5 Channels

Abstract: We studied the opening mechanism of Ca(2+)-permeable channels formed with mouse transient receptor potential type 5 (mTRP5) using Xenopus oocytes. After stimulation of coexpressed muscarinic M(1) receptors with acetylcholine (ACh) in a Ca(2+)-free solution, switching to 2 mM Ca(2+)-containing solution evoked a large Cl(-) current, which reflects the opening of endogenous Ca(2+)-dependent Cl(-) channels following Ca(2+) entry through the expressed channels. The ACh-evoked response was not affected by a depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 41 publications
1
41
1
Order By: Relevance
“…We designed a peptide (see Materials and methods) against this sequence to interrupt the binding of IP 3 R3 to TRPC2 and analyzed its effect on the chemosignal response over time in musk turtle VSNs, and found that 10·mol·1 -1 peptide nearly abolished the chemosignalactivated current by 10·min. The use of a peptide to disrupt the interaction between the IP 3 R and a TRPC channel has been shown previously; in Xenopus oocytes, suppression of the mTRPC5 current was seen with preinjection of a peptide mimicking the IP 3 binding domain of the IP 3 R (Kanki et al, 2001). These results indicate that there is a functional role for the IP 3 R in the VNO of the musk turtle.…”
Section: Discussionsupporting
confidence: 65%
“…We designed a peptide (see Materials and methods) against this sequence to interrupt the binding of IP 3 R3 to TRPC2 and analyzed its effect on the chemosignal response over time in musk turtle VSNs, and found that 10·mol·1 -1 peptide nearly abolished the chemosignalactivated current by 10·min. The use of a peptide to disrupt the interaction between the IP 3 R and a TRPC channel has been shown previously; in Xenopus oocytes, suppression of the mTRPC5 current was seen with preinjection of a peptide mimicking the IP 3 binding domain of the IP 3 R (Kanki et al, 2001). These results indicate that there is a functional role for the IP 3 R in the VNO of the musk turtle.…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, recent evidence indicates that there is an important functional requirement of InsP 3 Rs for the TRPC5 channel (32). Using DT40-InsP 3 R Ϫ/Ϫ cells transiently cotransfected with TRPC5 and eYFP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in addition to supporting TRPC4 function, PIP 2 also exerts a tonic inhibition on the channel. (21,(24)(25)(26)(27)(28)32). To determine if IP 3 Rs are involved in TRPC4 activation, we applied the IP 3 R inhibitor heparin (3 mg/mL) by intracellular dialysis and found that most cells failed to respond to DAMGO and subsequent application of CCh (Fig.…”
Section: Trpc4 Activation Requires Coincident G I/o Stimulation and Plcmentioning
confidence: 99%